The learning organisation: conditions of possibility in a feminist NGO. Issue 1 (2nd January 2016) - de Wet, Jacques P.; Schoots, Jonathan
ABSTRACT: Amidst criticism of the concept of "the learning organisation" there is a perspective which is both critical of, and open to, innovative ways of developing the notion of a learning organisation. This article contributes to this perspective by examining the learning practices of a feminist NGO which operates across Southern Africa. The ways in which this NGO has interpreted the idea of a learning organisation and put it into practice are an example of a bottom-up approach which is informed by humanism. The findings of this qualitative study demonstrate both innovative possibilities for organisational learning and potential pitfalls.